Thyroid Dysfunction and Male Reproductive Physiology - Patel, Neal; Kashanian, James A. (Seminars in Reproductive Medicine, 2016)
Normal thyroid physiology is paramount for the proper development and important for the maintenance of male reproduction. Both short- and long-term deviations in thyroid hormone levels have been shown to alter male reproductive function on a micro- and macroscopic level. Thyrotoxicosis and hypothyroidism are associated with changes in spermatogenesis, semen quality, levels of sexual hormones, and erectile function. However, the degree to which thyroid dysfunction is clinically responsible for male infertility has not been clearly elucidated.
Keywords: male infertility; sperm; semen; thyroid; hypothyroidism; hyperthyroidism